Challenges and Opportunities forInternational Indigenous Adaptation Network - Worou, Nadine (International Livestock Research Institute, 2025)
This presentation highlights the central role of indigenous peoples and pastoral communities in climate adaptation, emphasising climate justice and sovereignty as conditions for effectiveness and equity. It describes how integrating local knowledge with Western science strengthens resilience: land restoration, marking transhumance corridors, reducing farmer-herder conflicts, income-generating activities, and disseminating climate advisories in local languages through local channels. The experience of the Community of Practice in Senegal (co-production of agro-climatic advice for livestock farming, hosted by national institutions) and pastoral practices in Kenya illustrates measurable impacts (e.g. reduced livestock mortality during droughts). The presentation also analyses structural barriers to access to finance (complex procedures, low recognition of knowledge, land tenure insecurity, overly short financing periods) and calls for adapted, longer-term mechanisms rooted in indigenous knowledge systems.